2019
DOI: 10.1080/03075079.2019.1689385
|View full text |Cite
|
Sign up to set email alerts
|

Assessment for distinctiveness: recognising diversity of accomplishments

Abstract: Universities have responded to the expansion of higher education and restructuring of the labour market by redesigning curriculum to better emphasise transferable skills and embed pedagogies that contribute to graduate employability. However, the ways in which universities judge and share achievement still provides poor evidence of what students can do or the skills and personal attributes that inform job recruitment decisions. Furthermore, assessment provides little opportunity for students to develop the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The findings reveal that the most applied methodologies in graduate employability literature are case studies, semi-structured questionnaire, and content analysis (Bilsland et al, 2019; Holdsworth et al, 2020; Jorre de St Jorre et al, 2019; Nghia et al, 2019; Sandri et al, 2018a; Schaefer et al, 2019). Only a few studies have used theoretical review technique (Clarke, 2018; Ramsgaard & Østergaard, 2018) and thematic analysis (Halibas et al, 2020; Hammer et al, 2018).…”
Section: Discussion and Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings reveal that the most applied methodologies in graduate employability literature are case studies, semi-structured questionnaire, and content analysis (Bilsland et al, 2019; Holdsworth et al, 2020; Jorre de St Jorre et al, 2019; Nghia et al, 2019; Sandri et al, 2018a; Schaefer et al, 2019). Only a few studies have used theoretical review technique (Clarke, 2018; Ramsgaard & Østergaard, 2018) and thematic analysis (Halibas et al, 2020; Hammer et al, 2018).…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…Jorre de St Jorre et al (2019) critically examined the assessment process of graduates and found that there is potential mismatch in what expectations universities have and how they wish to achieve those. Their findings reveal that there should be four principles which will assess the achievements of universities in graduate employability and outcome-based learnings: opportunities for demonstration of distinct and personalized achievement, assessment to foster evaluative judgment, multiple portrayals of achievements, and meaningful evidence of the achievement.…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…Whilst there is a need to view assessment as certifying learning, assessment also highlights to students what is important to learn, and can act as a vehicle for students to develop their unique capabilities and confidence in those areas (Jorre de St Jorre et al, 2021). Within this conception of assessment as contributing to learning, assessment can also support the development of graduate attributes: 'a range of skills beyond those that are discipline-specific, such as those described as life-long learning, generic, transferable or 'soft' skills.'…”
Section: Inclusive Assessment Could Develop Graduate Attributesmentioning
confidence: 99%
“…Student learning and skill development in higher education are best achieved in authentic learning opportunities (Broadbent et al, 2018;Jorre de St Jorre et al, 2019). Leading scholars on experiential learning such as A. Y.…”
Section: Experiential Learning In Large Classesmentioning
confidence: 99%